Functional outcomes and clinical characteristics of children discharged from pediatric intensive care unit of a low- and middle-income countries: A single-center prospective observational cohort study from Rwand - Richard Gatera; Samantha Strelzer; Febronie Mushimiyimana; Françoise Nizeyimana; Christian Umuhoza; Aimable Kanyamuhunga; Lisine Tuyisenge; Cliff O’Callahan (Journal of Pediatric Critical Care)
Background: The development of pediatric intensive care units (PICUs) has contributed to the improvement in the survival of critically ill children; however, the long-term functional outcome of these children is often unknown in many low-/middle-income countries including Rwanda. This study aimed to describe incidence and type of long-term functional outcomes and associated clinical characteristics among PICU survivors during a 5 years’ period (2015–2019). Subjects and Methods: This was a single-center, prospective observational cohort study conducted in the PICU of University Teaching Hospital in Rwanda. A Pediatric Cerebral Performance Category (PCPC) and Pediatric Overall Performance Category (POPC) scales were used to screen for long-term functional outcomes. The results were evaluated by telephone interview and statistically analyzed using logistic regression. Results: Out of 158 children, 53.2% had overall disability while 33.6% had some level of cognitive disability after PICU discharge. Out of 41 (2`5.9%) deaths during study period, three (7.3%) occurred during the hospital stay, while 8 (19.6%) occurred after the first year of hospital discharge. Disability screened by two scales, PCPC and PCOC, was comparable for mild (13.3% vs. 23.4%), moderate (11.4% vs. 20.3%), and severe (5.1% vs. 5.7%) categories. PICU admission for patient with at least one preadmission comorbidity had significantly greater disability at discharge (P < 0.05). Conclusions: Despite a high survival rate, residual functional disability is prevalent among children after discharge from the PICU in Rwanda. The presence of at least one preadmission comorbidity was independently associated with greater disability at discharge.